3. Identification And Prevalence Of Endoparasites In Lovebird (Agapornis Fischeri) Sold In Banda Aceh - Muhammad Dicky Zulmi; Teuku Reza Ferasyi; Farida Farida; Winaruddin Winaruddin; Eliawardani Eliawardani; Zuhrawaty Zuhrawaty (Universitas Syiah Kuala, 2020)
This study aims to identify the types and rate the prevalence of endoparasites in lovebirds (Agapornis fischeri) sold in Banda Aceh City. The study has been carried out in Banda Aceh from December 2018 to January 2019. The samples used in this study were 60 samples of lovebird feces taken from pet bird traders from the Ulee Kareng market (2 locations), Seutui market (3 locations), and Neusu market (7 locations). The results obtained were analyzed descriptively. The results of the examination showed that the prevalence of lovebirds sold in Banda Aceh City was 10%. In detail, endoparasites worms from the genus of Ascaridia sp, Heterakis sp, and Capillaria spp were found, with a prevalence of 5%, 3.33%, and 1.67% respectively. Thus it can be concluded that there is endoparasites worms infection in lovebirds sold by traders in Banda Aceh City